2009
DOI: 10.1007/s12223-009-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Yersinia pseudotuberculosis outer proteins (Yops) in murine humoral immune response

Abstract: The infection of mice with the wild-type (WT) strain of Y. pseudotuberculosis did not induce polyclonal activation of B lymphocytes. Suppression in the production of certain isotypes of Ig was observed, provoked mainly by YopH, YopJ and YpkA. The WT strain induced a progressive increase in the serum-specific IgG, which peaked after 4 weeks after infection, IgM being produced only after 1 week. Autoantibodies against phosphorylcholine, myelin, thyroglobulin and cardiolipin could be detected in the serum of mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Results of previous studies have suggested that YopJ/P activity can inhibit the development of adaptive immune responses in mice infected with Yersinia (32,37,65,67). However, a caveat of these previous studies is that immune responses in mice infected with yopJ or yopP mutant strains were compared to those of mice infected with other attenuated Yersinia strains but not to those infected with wild-type strains (32,37,65,67).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Results of previous studies have suggested that YopJ/P activity can inhibit the development of adaptive immune responses in mice infected with Yersinia (32,37,65,67). However, a caveat of these previous studies is that immune responses in mice infected with yopJ or yopP mutant strains were compared to those of mice infected with other attenuated Yersinia strains but not to those infected with wild-type strains (32,37,65,67).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, although YopJ/P plays a reproducible role in systemic colonization following bacterial spread from the intestinal tract, its role in virulence remains variable and likely will depend heavily on the conditions of the experiment, including, most critically, the strains of Yersinia and mice used. On the other hand, evidence is accumulating that YopJ activity is not required for virulence or tissue colonization by Y. pestis in bubonic, pneumonic, or septicemic plague models (33,63,73,74) or Y. pseudotuberculosis when mice are infected by a route (e.g., intraperitoneal or intravenous) that bypasses the intestinal phase (2,37). Why YopJ/P specifically promotes systemic colonization following intestinal Yersinia infection is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation